Developing Students' Mathematical Communication Skills on Geometric Number Patterns Through Group Investigation and Peer Teaching - Noviana, Anne Putri; Nurhayati, Elis; Rustiana, Ratna (International Journal of Geometry Research and Inventions in Education, 2024)
This study aims to determine the improvement in students' mathematical communication skills in learning geometric number patterns through the Group Investigation model with the Peer Teaching method. The study uses an experimental method. The population in this study includes all 8th-grade students in the middle school. The sample consists of all students in classes VIII-G and VIII-I. The research instrument used to collect data is a test on mathematical communication skills specifically designed for geometric number patterns. Based on the data obtained, it can be concluded that the experimental class performed better than the control class. In the experimental class, there were 4 students with low ability, 16 students with moderate ability, and 14 students with high ability. Meanwhile, in the control class, there were 7 students with low ability, 24 students with moderate ability, and 3 students with high ability.